The Influence of Influencer Credibility on Brand Loyalty with Brand Trust as a Mediating Variable : Study on Make Over Lipstick Product Customers in Denpasar City - Rena Wilona Rahma; Gede Suparna (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2025)
Competition in the cosmetics industry in Indonesia is getting tougher, prompting local brands to develop effective marketing communication strategies to increase consumer loyalty. Make Over, as one of the popular local lipstick brands, leverages collaboration strategies with credible beauty influencers, such as Tasya Farasya, to build positive perceptions and increase consumer engagement. This study aims to analyze the influence of influencer credibility on brand loyalty and examine the mediating role of brand trust in the relationship. This research was carried out in Denpasar City by involving 180 respondents who were consumers of Make Over lipsticks. The sampling technique used is purposive sampling, with certain criteria to ensure the relevance of respondent participation. Data collection was carried out through questionnaires that were distributed online and offline. The collected data was analyzed using path analysis techniques with the help of SPSS software version 29.0.2.0. The results of the analysis show that influencer credibility has a positive and significant influence on brand loyalty and brand trust. In addition, brand trust has been proven to have a positive and significant influence on brand loyalty. Another important finding is that brand trust partially mediates the relationship between influencer credibility and brand loyalty, suggesting that the influence of influencer credibility on loyalty is not only direct, but also through the formation of trust in the brand. Thus, this study confirms that collaboration with influencers who have high reputation, expertise, and credibility can be an effective strategy to increase consumer trust and loyalty towards cosmetic brands. Therefore, choosing the right influencers is essential in a marketing communication strategy to build long-term relationships with consumers.